Uso da simulação microscópica para a avaliação do tempo de viagem de sistemas de transporte público por ônibus em corredores de tráfego misto - Sousa, Vanessa Vieira de (2016)
Currently, the microsimulation is presented as one of the main tools of transportation system analysis. The potential of its use in related aspect analysis to operation of urban public transport systems has not been reviewed in detail, specifically in regard to the proper representation of geometrical and operational attributes, vehicle movement and their mixed traffic interaction. Studies with this tool for public transportation modeling by bus have been focused on impact analysis of this mode on traffic flow. From this context, this research aims to evaluate the use of microsimulation of public transport modeling by bus in Brazilian urban areas. The main elements present in such systems were observed to understand their influence on its operational performance and how they should be represented in traffic microsimulators, since the microscopic simulation is the ideal tool for analyzing such components and the interactions between vehicles and passengers. The operational performance modeling of public transportation by bus of two microsimulators most used today in technical and academic means was investigated and found advantages and disadvantages in AIMSUN and Vissim. A bus lane in the city of Fortaleza was used as a case study, which were analyzed more deeply the functionalities of Vissim, simulator that showed the most complete in public transportation system by bus simulations, and the effort needed to calibrate your car following model. The results show the importance of collecting data on breakpoints, because the effective coding of this component strongly influences on the bus travel times and make the calibration process easier. It was also concluded that, in spite of some limitations, the microsimulation consists in an effective tool for public transportation studies, but obtaining from the field values of the largest possible quantity of input parameters is crucial. These values can vary significantly depending on the area of study or type of public transport operation. Beyond the reach of the main objective of this work, is expected to ease to analysts the choice of a simulator for their specific studies and show which limitations and that you can overcome these microsimulators limitations.